Exact determination of beams with given buckling loads - MORASSI, ANTONIO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2014)
We present an analytical procedure for the determination of EulerBernoulli beams which have given values of the first N buckling loads. The result is valid for pinned-pinned end conditions and for beams with regular bending stiffness. The analysis is based on a reduction of the buckling problem to an eigenvalue problem for a vibrating string, and uses recent results on the exact construction of Sturm-Liouville operators with prescribed natural frequencies